EFEKTIFITAS EKSTRAK DAUN KIPAHIT PADA BERBAGAI FASE PERTUMBUHAN TANAMAN SAYURAN DAUN TERHADAP HAMA DAN PENYAKIT, PERTUMBUHAN DAN PRODUKSI TANAMAN - Sukrianto, Sukrianto; Tanjung, Dian Diani; Fitriani, Askiah; Handini, Apryanti (Institute of Computer Science (IOCS), 2025)
Kipahit leaves have potential as botanical pesticide, however the correct application time during plant growth phase still rarely done. This research was conducted to obtain information on appropriate growth phase for application, especially on green mustard and spinach plants. Research was in November-December 2021 at Pamtasa Farm Hydroponic Garden, Depok, West Java, altitude of ±55 m above sea level. Pesticide ingredients are kipahit leaves and water, as well as other equipment needed to make vegetable pesticides. Research used randomized complete group design with six spray time treatments, namely: no spraying (P0); seeding phase (P1); rejuvenation phase (P2); maturation phase (P3); rejuvenation and maturation phase (P4), and seeding, rejuvenation and maturation phase (P5). Each treatment was repeated four times. Data were analyzed using Minitab version 16 software using one-way ANOVA parameters with a Tukey test level of 5%. Parameters measured include identification pests and diseases, percentage plant damage, plant height, leaf area, gross weight and plant consumption weight. Results showed the application at the seeding phase significantly increased height of spinach by 20.82%, leaf area of ??mustard by 18.62%, gross weight by 31.64% and consumption weight by 46.98% of mustard, gross weight by 28.06% and consumption weight by 23.51% of spinach.